LINGUACULTURAL FEATURES OF FOOD RELATED VOCABULARY IN ENGLISH AND UZBEK - Kamolova Rushana Ibodovna; Yusupova Shoira Botirovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article lights up the linguacultural features of food-related vocabulary in English and Uzbek languages. It explores how cultural values, traditions, and national identity are reflected in the naming, use, and perception of food items. The study is grounded in linguoculturology and semantics, focusing on culturally marked food terms, metaphors, and idiomatic expressions associated with food.